Development of New Frothers through Hydrodynamic Characterization of Frother Chemistry - J. A. Finch (Canadian Institute of Mining, Metallurgy and Petroleum, 2007)
"Much progress has been made over the last several years in the ability to measure flotation cell hydrodynamic parameters in both the laboratory and plant. These techniques have allowed fundamental research to proceed to determine the effects that frother chemistry has on the main hydrodynamic parameters (gas hold up, bubble size) as well as on the amount of froth generation and water content of froth. A research program was begun that brought together a team consisting of private companies and a University with expertise in hydrodynamic characterization (McGill), flotation reagent applications (Flottec) and chemical synthesis (Sasol N.A.) with the purpose of characterizing frother chemistries with two goals in mind: Determine which frother chemistry can provide optimized cell hydrodynamics; and, create new frother chemistries with specific hydrodynamic properties.This paper describes the key steps that were taken that led to the development of new frother chemistry for use in flotation.The first step was the characterization of the major frother chemical families in a two phase system. The parameters measured were gas hold up, bubble size, froth height and water carrying rate at different concentrations and gas velocities.Analysis of the data indicated that definite patterns existed between frother chemistry and hydrodynamics and showed that frothers could be grouped into classes. More importantly, by modifying known frothers through chemical reaction it was shown that these frothers could be moved from one class to another. As a result of this better understanding of the interdependence of hydrodynamic and chemical properties, a new frother chemistry was proposed that was predicted to perform similarly to MIBC.The new frother was synthesized and hydrodynamic testing confirmed that the chemical performed similar to MIBC. Laboratory flotation tests were conducted on two different ore types that also confirmed the similar performance of the new chemical and MIBC. Subsequently, the new product was placed on a plant for a short period of time. The results showed that the product was an excellent frother but increased the flotation rate slightly more than MIBC at the same addition rate.Further research showed that the new frother chemistry was a family of products. By changing the reaction the resultant products could be made to be slightly weaker or stronger than MIBC but that this chemistry cannot provide hydrodynamic/froth characteristics similar to strong frothers like glycols and glycol ethers. Further work is planned to conduct longer plant trials to confirm the efficacy of this new frother family."